A graphene-based electro-thermochromic textile display - Ji,X; Liu,W; Yin,Y; Wang,C; Torrisi,F (Journal of Materials Chemistry C, 2020)
Electronic textiles (e textiles) are rapidly emerging as key enablers for wearable electronics. Graphene and 2D materials have played a major role in enabling truly wearable e-textiles. Here we demonstrate a textile-based display using the Joule's heating of a screen-printed, few-layer graphene ink to drive the colour switching of thermochromic polyurethane on a cotton fabric. The average temperature of the few-layer graphene ink on the fabric was voltage-controlled reaching about 43 °C in 45 s at a bias of 12 V and a recovery of <20 s with negligible degradation after several heating/cooling cycles. This is used to demonstrate several electro-thermochromic textile displays, thus representing a breakthrough in e-textiles technology.